La Question du Home Rule écossais, 1880-1914 - Christian Auer (Revue Française de Civilisation Britannique)
The parliamentary debates inspired by the introduction of motions and bills in favour of Scottish Home Rule between 1889 and 1914 are a remarkable source of information to assess the arguments that were put forward in favour and against Home Rule. Studying these debates allows to understand why the question of Home Rule came to dominate Scottish politics towards the end of the nineteenth century. This article also attempts to determine the weight of nationalism in the Scottish claims and to analyse the ins and outs of the schemes proposed by the Scottish Home Rulers — notably the way power was meant to be shared between the Imperial Parliament and the local parliaments. The main arguments and counter-arguments that were used respectively by the supporters and opponents of Scottish Home Rule will be examined, which will lead us to discuss the correlation between Irish Home Rule and Scottish Home Rule. The important question of the Scottish Union will also be focused on: some believed Scottish self-government was compatible with the preservation of the Union while others believed Home Rule threatened this Union. The article concludes by highlighting some of the reasons that may explain the ultimate failure of Scottish Home Rulers to obtain self-government for Scotland.